Armadilhas no labirinto: escolarização e trabalho docente desafiados pelo Pacto da Educação em Goiás - Almeida, Rosivaldo Pereira de (2018)
This work is part of the Education, Teacher Training and Educational Work Line of the Post- Graduation Program in Education, Federal University of Goiás, and aims to critically understand the conceptions of schooling and teaching work engendered in the Business Pact for Education in Goiás. It is a documentary and bibliographical research made from the analysis of document contents: Pact for Education: a better future demands changes (2011); Recognition Program: Education, the merit is yours - criteria and procedures (2012); Reference Curriculum of the State Educational Network of Goiás: experimental version (2012) and Management Circuit Notebook - Young Future Project: principles and method - Formative Path of School Management for Learning Outcomes (2016). From the cross analysis and interlacing of concepts identified in the documents, a process of technification of teaching work and schooling was evidenced as a reified treinality. The Recognition Program and the Management Circuit of the Unibanco Institute, implemented in the state public network of Goiás, as well as the Reference Curriculum, linked to a data base operationalized through virtual platforms, are effective control mechanisms and management of the pedagogical work and schooling. In our understanding, through the analysis of the documentary corpus, a conception of practicing schooling and the teachers' complete estrangement from the work of teaching are materialized. From the reality of the system of schooling of the state public network it is possible to perceive, in this current phase of accumulation, that capital promotes reification, using the processes of schooling and the technification of teaching work. They are theoretical references that contribute to the theoretical basis of our study: Hobsbawm (1995); Castel (2003); Araújo Júnior (2013); Enguita (1989); Gentilli (1999); Anderson (2000); Harvey (2005); Bourdieu (1998); Moraes (2011); Libâneo (2011); Silva (2013); Silva and Siqueira (2016); Magalhães (2014); Algebaile (2009); Peregrino (2006); Oliveira (1984); Harvey (1993); Miranda (2006, 2005) and Resende (2009).